Upaya Peningkatan Kualitas Kompetensi Pedagogik Tutor di Pusat Kegiatan Belajar Masyarakat (PKBM) Kecamatan Batang Masumai Kabupaten Merangin Provinsi Jambi - Uying Hapid Alatas; Fithri Azni; Aksul Dewi Fikra (CV. Ulil Albab Corp, 2023)
Tutor as one important component in the education system, it acts as a good teacher. Tutor is a private tutor, lecturer or tutor extra / teaching. Where the tutor is a term for those who teach in non-formal education, despite being a tutor is a tutor in formal education. Tutor is the citizens who have advantages (expertise, skills, abilities) in the field of knowledge and skills, particularly in teaching and managing livelihood, and who are interested and willing to become a tutor, has a high spirit of dedication in guiding the learners in study groups to improve knowledge sesamanya.Kompetensi pedagogic skills tutor still inadequate particularly in regard to their field. Many of them are not or less capable of presenting and delivering education that actually qualified. To improve pedagogical tutor, according to Slamet (1999) there are four fundamental business should be done in an educational institution, which is to create